Ulat pulat - Amra, Alam; Maliha, Rao (Book Group Karachi, 2002)
"Ulat Pulat" is a whimsical children's book that turns the world upside down. Through playful rhymes and vibrant illustrations, this book encourages young readers to think creatively and challenge conventional thinking. Join the fun as everyday objects and situations take on unexpected and humorous twists.